Positive psychology and the search for happiness at work - Porras Velasquez, Nestor Raul (Majalah Kesehatan Indonesia, 2024)
This study aims to develop an analysis model and psychosocial and cultural interventions that specifically adapt and extend Martin Seligman's proposed framework of happiness in the workplace. Focusing on the work context in Colombia, this research poses the question: "How can a model adjusted to the cultural and social context of Colombia enhance understanding and practices of happiness at work, compared to Seligman's model?". In terms of methodology, this research employs comprehensive document analysis, selecting sources based on their relevance to the positive psychology framework and its application in the Colombian work environment. Selection criteria include the novelty of the research, relevance to the local work context, and contributions to the understanding of happiness at work. The analysis process incorporates a qualitative approach to identify common themes and specific nuances related to work subjectivity and mental health. The research results indicate that the adjusted analysis model and interventions provide new insights into the dynamics of happiness at work in Colombia, highlighting the importance of cultural and contextual factors in designing and implementing interventions. Specifically, this model reveals that approaches considering local social and cultural values as well as specific economic challenges can be more effective in promoting positive work subjectivity and mental health. Implications suggest that adapting the workplace happiness model to include specific cultural and social considerations can enhance the effectiveness of psychosocial and cultural interventions. This research lays the groundwork for developing more focused and relevant strategies to improve worker well-being in Colombia and similar contexts.